In-vitro inhalation bioavailability estimation of Metal(oid)s in atmospheric particulate matter (PM2.5) using simulated alveolar lysosomal fluid: A dialyzability approach. (15th January 2023) - Novo-Quiza, Natalia; Sanromán-Hermida, Silvia; Sánchez-Piñero, Joel; Moreda-Piñeiro, Jorge; Muniategui-Lorenzo, Soledad; López-Mahía, Purificación
Abstract: A novel in-vitro method, by using synthetic body fluids, human physiological conditions and a simulated air-blood barrier (by using a dialysis membrane) has been developed and applied to assess in-vitro inhalation bioavailability of metal(oid)s associated to particulate matter (PM2, 5 ) samples collected from an industrial site of the Northwest of Spain. A validated analytical methodology based on inductively coupled plasma mass spectrometry (ICP-MS) was used to analyse metal(oid)s concentrations in bioavailable fractions. This approach would be a more realistic human health risk assessment since considering processes that occur in human body in contrast the overestimation derived from current models (which consider environmental concentrations). Metal(oid)s such as Cu and Mo seemed to be the most bioavailable (mean in-vitro bioavailability ratios higher than 70%); Ba, Cd, Mn, Pb, Rb, Sb, Sn, V and Zn shown mean ratios between 20 and 60%, while low in-vitro bioavailability ratios (less than 20%) were observed for metal(oid)s such as Al, Co, Cr, Fe, Ni, Ti, and Tl. Health risk assessment via inhalation based on hazard carcinogenic and non-carcinogenic indexes (HIc and HInc, respectively) were performed considering three exposure scenarios using both inhalation bioavailable and total metal(oid)s concentrations in PM2.5 samples, suggesting no risk to human health. The influence of chemical composition on in-vitro bioavailability ratios was obtained, pointing out that inhalation ratios of Al, Ba, Cr, Cu, Fe, Ni, Pb and V seem to be affected by sea salt and/or crustal and/or biogenic and/or anthropogenic content of PM2.5 . Graphical abstract: Image 1 Highlights: Bioavailability of metal(oid)s was estimated by a simulated dialysis approach. High inhalation bioavailability ratios (>70%) were found for Cu and Mo. Low bioavailability ratios (<20%) were found for Al, Co, Cr, Fe, Ni, Ti and Tl. Bioavailability of some metal(oid)s seemed to be correlated with PM2.5 compositions. Health risks for PM2.5 -bound metal(oid)s via inhalation suggesting no risk to human.